Pengaruh Model Paikem Gembrot terhadap Hasil Belajar Matematika Siswa Kelas IV SD - Azra Aulannisa; Adisel Adisel; Fatrima Santri Syafri; Suryati Suryati (Journal of Elementary School (JOES), 2021)
This research aims to determine the effect of the PAIKEM GEMBROT model on mathematics learning outcomes for fourth grade students of SD Negeri 16 Pagar Alam. The sampling technique in this study is to use a saturated sample technique where all students are used as research samples. The researcher took class IV to serve as the research sample, totaling 27 students as the experimental class. The research design used in this study was only one group so it did not require a control class. Analysis of data testing using the t test, it can be seen through the normality test that was carried out previously with a significance value of 0.200> 0.05 and it was stated that the data were normally distributed. Furthermore, by conducting a t-test that students' mathematics learning outcomes got an average Pretest score of 68.78 and an average Posttest score of 78.04 with a descriptive conclusion that there were differences in student learning outcomes. Based on the output results of the Paired Sample T – Test, it is known that the significance value (Sig.) (2-tailed) is 0.000. Provided that if the significance value is 0.000 <0.05, then Ho is rejected and Ha is accepted. So it can be concluded that from the results Ha received means that there is an influence in the use of the PAIKEM GEMBROT model in fourth grade students of SD Negeri 16 Pagar Alam. Keywords: Influence, Paikem Gembrot, Math